1996
DOI: 10.1021/jp960977j
|View full text |Cite
|
Sign up to set email alerts
|

Designed Intramolecular Competition in a Chromophore−Biquencher Complex

Abstract: Competitive energy and electron transfer occur following excitation of the chromophore-biquencher [Re I (MebpyCH 2 OCH 2 An)(CO) 3 (MQ + )](PF 6 ) 2 (MebpyCH 2 OCH 2 An is 4-[(9-anthrylmethoxy)methyl]-4′-methyl-2,2′-bipyridine; MQ + is N-methyl-4,4′,-bipyridinium ion). Following excitation with a 392-nm, 4-ns laser pulse in 1,2-dichloroethane (DCE), the initial excited state energy is distributed in a ∼2:1 ratio between 3 An* and the lower lying Re II (MQ ‚ ) metal-to-ligand charge transfer (MLCT) excited stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Generally, it appears that the driving force of the MQ • →Re II electron transfer is only little dependent on the medium. This assumption is supported by the fact that the emission from the 3 MLCT(MQ) state of [Re(MQ + )(CO) 3 (bpy)] 2+ occurs at very similar energies in CH 3 CN and ClCH 2 CH 2 Cl, 1.88 and 1.78 eV, respectively, , and by very similar values of the difference between the potentials of the reversible MQ + /MQ • reduction and the quasireversible Re I /Re II oxidation in CH 3 CN, CH 2 Cl 2 , and THF: 2.46, 2.39, and 2.57 V, respectively. In conclusion, we assume that the driving force of the back reaction in all the solvents investigated lies within the range 2.1−2.3 eV.…”
Section: Resultsmentioning
confidence: 81%
“…Generally, it appears that the driving force of the MQ • →Re II electron transfer is only little dependent on the medium. This assumption is supported by the fact that the emission from the 3 MLCT(MQ) state of [Re(MQ + )(CO) 3 (bpy)] 2+ occurs at very similar energies in CH 3 CN and ClCH 2 CH 2 Cl, 1.88 and 1.78 eV, respectively, , and by very similar values of the difference between the potentials of the reversible MQ + /MQ • reduction and the quasireversible Re I /Re II oxidation in CH 3 CN, CH 2 Cl 2 , and THF: 2.46, 2.39, and 2.57 V, respectively. In conclusion, we assume that the driving force of the back reaction in all the solvents investigated lies within the range 2.1−2.3 eV.…”
Section: Resultsmentioning
confidence: 81%
“…Energy transfer occurs to give fac -[Re I [Mebpy-CH 2 OCH 2 ( 3 An*)](CO) 3 (MQ + )] 2+ . It is in competition with electron transfer to give fac -[Re II (Mebpy-CH 2 OCH 2 An)(CO) 3 (MQ·)] 2+ * …”
Section: Introductionmentioning
confidence: 99%
“…It is in competition with electron transfer to give fac-[Re II (Mebpy-CH 2 OCH 2 An)(CO) 3 (MQ‚ )] 2+ *. 13 In this manuscript, we explore a second competition, in this case between electron and energy transfer in fac-[Re I (dppz)-(CO) 3 (py-PTZ)] + (1, dppz is dipyrido[3,2-a:2′,3′-c]phenazine). Ligand structures are illustrated below.…”
Section: Introductionmentioning
confidence: 99%
“…Complex 2Re(BiPy‐Me) 2 containing viologen‐type N‐methyl‐4,4’‐bipyridinium ligand (MQ + ) demonstrates rich electrochemistry both in oxidation and reduction modes (Figure 8) due to availability of low lying filled and empty orbitals of the aromatic ligands and a variety of charge transfer processes, which may occur in these systems [65–74] …”
Section: Resultsmentioning
confidence: 99%
“…Complex 2Re(BiPy-Me) 2 containing viologen-type N-methyl-4,4'-bipyridinium ligand (MQ + ) demonstrates rich electrochemistry both in oxidation and reduction modes (Figure 8) due to availability of low lying filled and empty orbitals of the aromatic ligands and a variety of charge transfer processes, which may occur in these systems. [65][66][67][68][69][70][71][72][73][74] Application of several spectro-electrochemical techniques in the study of the [Re(N N)(CO) 3 MQ] 2 + complexes [67][68][69][70]75,76] showed that CV of this type of compounds commonly display four reversible one-electron reduction waves related to successive one and two electron reduction of the diimine and MQ…”
Section: Electrochemistrymentioning
confidence: 99%